A Hot-Area-Based Selfish Routing Protocol for Mobile Social Networks. (1st January 2013) - Gong, Haigang; Wang, Xiaomin
Abstract : Data delivery in mobile social network is a challenging task due to the nodal mobility and intermittent connectivity. It is natural to utilize the inherent social properties to assist in making forwarding decisions. However, existing routing schemes seldom consider selfishness of nodes and assume that nodes are willing to forward messages for others. In the real world, most people are selfish and nodes attached to people behave selfishly too. Based on the regularity of human behavior, we propose a hot-area-based selfish routing protocol (HASR) tailored for mobile social networks in this paper. Data transmission is based on the active degree of the node, which is calculated by the weight of hot areas that nodes will visit, when there are no selfish nodes. When nodes behave selfishly, routing decision is made by the contribution index that indicates the contributions to data transmissions of the network made by nodes. Simulation results show that HASR performs better when nodes behave selfishly.